Early ultrastructural changes of thymocytes in T-2 toxicated mice - Quiroga, María Alejandra (1993)
Subcellular changes of mouse thymocytes after T-2 intoxication were observed for up to 48 hours after injection (HAI). The following changes were observed mainly in cortical lymphocytes at 8 and 16HAI: (1) nuclear projections, (2) nuclear macrocleft, and (3) characteristic features of apoptosis. Conclusively, it is suggested that apoptosis is partially involved in the early development of thymic lesions by T-2 toxin.